Genetic and Phenotypic Relationships Between Mcnally Model Parameters and Egg Production Traits - Oni, O. O.; Abubakar, B.Y.; Dim, N.I.; Asiribo, O.E.; Adeyinka, I.A. (International Journal of Poultry Science, 2006)
The monthly egg production data of Rhode Island Red (strain A) and White (strain B) chickens were used to estimate the genetic and phenotypic relationships between egg production traits and curve parameters obtained from fitting the McNally model to 52-wk laying records. A total of 356 and 292 records for strains A and B, respectively, were included in a variance component analysis of a two factor nested classification - dams within sire. The estimates of heritabilities and correlations for production traits were moderate to high, while the values obtained for the curve parameters varied from low to moderate. The estimates of correlations of part-productions with 52-week total were comparatively higher than the values obtained for curve parameters with 52-week total. The low estimates of heritability obtained for curve parameters indicated that it would be better to select on functions of the parameters (such as total production or part-year production), which had higher estimates, rather than individual curve parameters. The high genetic correlation between part-year production and total annual production suggests that selection for the latter based on the former would not diminish genetic progress. The decreased generation interval that would result from selection on part record will probably more than offset the loss in efficiency if records are taken for about half of the full laying year.